Tools and Mechanisms for Rural Area Development in the State Economic Security Policy System - Hubeni, Yurij; Boiko, Vitalii; Olishchuk, Petro (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2016)
The article studies the regional-sectoral dimension of the correlation between the development of rural areas and the economic security of the state. The structural approaches are determined by the positioning of the economic mechanism of rural area development in the system of state economic security. The paper identifies key risks and describes their destabilizing impact on rural area development in the context of the economic, social and environmental spheres. A set of tools and mechanisms are worked out to stimulate the development of rural areas within the framework of the state policy of economic security; these the key mechanisms are administrative and management, organizational and economic, socio-humanitarian, logistics and infrastructural, and environmental protection.